Design of the phonocardiography appliance for coronary artery disease diagnosing and monitoring : business perspectives analysis of innovative medical technologies for cardiovascular diseases in Finland - Lazarev, Kirill (My University, 2019)
The topic of this study is the application of modern medical technology to cardiovascular conditions. The main purpose of that research is to evaluate myocardium disorders from the versatile perspectives and propose the design of a socially-demanding and financially-efficient technological solution targeted to coronary artery disease (CAD) diagnosing and monitoring. Phonocardiography and audial CAD detection are discussed as innovative methods for personalized healthcare applications and based on that, digital product design is developed in the form of functional specification, wearable device model, iOS and WatchOS applications interface architecture. In addition to the diseases study, myocardium signals acquisition discussion and to device design itself, market research is conducted. It is focused on medical technologies segment in general and cardiological systems in particular. Finland and Nordic Europe are the major covered regions, while global trends are outlined to collect the vision on the general market tendency. Core assessment topics are medical technology product distribution models, investment potential and development barriers. The final result could be used as a foundation for further product development and as an overview or guidelines for businesses interested in healthcare Internet-of-Things and cardiological systems.
Keywords: Coronary artery disease, phonocardiography, medical technology, iOS, wearable